DISCARDS OF THE INDONESIAN TUNA LONGLINE FISHERY IN INDIAN OCEAN - Bram Setyadji; Budi Nugraha (Indonesian Fisheries Research Journal, 2013)
Incidental by-catch and associated discarding are difficult to estimate on the basis of logbook information because they are poorly reported by fishing masters and their importance varies with several interrelated factors. The purpose of this paper is to inform the commonly discarded fishes of the Indonesian tuna longline fishery in the Indian Ocean. The study was carried out during 2010 – 2011 following six commercial tuna longline vessels based in Port of Benoa. Discards composition was dominated by longnose lancetfish and pelagic stingrays which composed almost half of total discards. Almost half of total catch are discards and half of discards are disposed dead or dying.